Considerations regarding the procurement of public infrastructure projects - Arata Delgado, Carlos Enrique (2023)
In this text, the author intends to explain, in detail, which elements must be taken under consideration at the moment of deciding to acquire companies linked to public infrastructure projects.In this way, the author develops from general elements to be taken into consideration for this purpose (such as due diligence), to more specific issues related to each type of company (such as environmental and regulatory aspects, etc.).